Effect and safety of escitalopram in the treatment of depressive disorder in patients with myocardial infarction: A prospective study - Sujata Sethi; Narender Rohilla; Kuldeep Lallar (Journal of Mental Health and Human Behaviour, 2016)
Background: The top two contributors to the worldwide burden of disease are predicted to be ischemic heart disease (IHD) and major depression. Patients with established IHD are at risk to develop depression. Major depression is common among patients recovering from myocardial infarction (MI). As depression can worsen the prognosis of cardiac patients, it might be possible to improve the prognosis by treating the depression with antidepressants. Aim: The index study aimed to find the prevalence of depressive disorder in adult patients with MI admitted to the cardiology unit and to examine the outcome as regards to the effect and safety of escitalopram as per the treatment regime routinely followed for the treatment of depression in such patients. Methods: One hundred consecutive patients with an established diagnosis of MI admitted to the Department of Cardiology constituted the study sample. Patients who qualified for the major depressive disorder were then treated with escitalopram. Results: The overall prevalence of depression in patients with MI is 22%. The study highlights that depression in the post-MI period is common and responds well to antidepressant treatment. Escitalopram could be an effective and safe antidepressant for the treatment of depression in patients with MI. Conclusion: The study highlights that depression in post MI period is common and escitalopram seems to be an effective and safe antidepressant for the treatment of depression in MI patients.